2014
DOI: 10.1002/adem.201400151
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Deposition of Energetic Polymer Nanocomposites with High Mass Particle Loadings: A Prelude to 3D Printing of Rocket Motors

Abstract: One of the challenges in the use of energetic nanoparticles within a polymer matrix is the difficulty in processing by traditional mixing methods. In this paper, electrospray deposition is employed to create high loadings of aluminum nanoparticles (Al-NPs) in polyvinylidene fluoride (PVDF) reactive composite films. The deposited films containing up to 50 wt% Al are found to be crack free and mechanically flexible. Thermochemical behavior characterized by thermogravimetric (TG) and differential scanning calorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 48 publications
(48 reference statements)
5
89
0
Order By: Relevance
“…Etching can be used to prepare nanostructured substrates (fuel) into which an oxidizer can be deposited [23]. Suspension of particulates coupled with ink-jet writing has also been used to fabricate energetic films [24][25][26]. In general, these and other sophisticated methods produce an intermixed material with a range of domain sizes and morphology, each coming with a range of advantageous and detrimental properties for a given application.…”
Section: Introductionmentioning
confidence: 99%
“…Etching can be used to prepare nanostructured substrates (fuel) into which an oxidizer can be deposited [23]. Suspension of particulates coupled with ink-jet writing has also been used to fabricate energetic films [24][25][26]. In general, these and other sophisticated methods produce an intermixed material with a range of domain sizes and morphology, each coming with a range of advantageous and detrimental properties for a given application.…”
Section: Introductionmentioning
confidence: 99%
“…[21] In a typical experiment, 141.2 mg of Bi(IO 3 ) 3 nanoparticles, 107.9 mg Al-NPs, 200 mg PVDF, and 4.5 mg AP was dissolved in 4 mL DMF. In our previous work, we find that a small quantity of AP in the precursor can significantly improve the morphology and mechanical property of the films.…”
Section: Preparation Of Precursorsmentioning
confidence: 99%
“…Our previous research [21] showed that Al/ PVDF could be fabricated in a direct write mode to create 3D printed propellant. In this study, we have so far shown that Bi(IO 3 ) 3 when reacting with Al can generate both heat and biocidal iodine.…”
Section: Bi(io 3 ) 3 /Al/pvdf Composite Filmsmentioning
confidence: 99%
See 2 more Smart Citations